2016
DOI: 10.1128/aem.00623-16
|View full text |Cite
|
Sign up to set email alerts
|

(p)ppGpp-Dependent Persisters Increase the Fitness of Escherichia coli Bacteria Deficient in Isoaspartyl Protein Repair

Abstract: The L-isoaspartyl protein carboxyl methyltransferase (PCM) repairs protein damage resulting from spontaneous conversion of aspartyl or asparaginyl residues to isoaspartate and increases long-term stationary-phase survival of Escherichia coli under stress. In the course of studies intended to examine PCM function in metabolically inactive cells, we identified pcm as a gene whose mutation influences the formation of ofloxacin-tolerant persisters. Specifically, a ⌬pcm mutant produced persisters for an extended pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The relationships between the stringent response alarmone (p)ppGpp and persistence are dissimilar in different bacteria ( Conlon et al, 2016 ; VandenBerg et al, 2016 ; Pacios et al, 2020 ). Previous research from our laboratory indicated that B. abortus was capable of forming multi-drug tolerant persister cells ( Liu et al, 2023 ) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationships between the stringent response alarmone (p)ppGpp and persistence are dissimilar in different bacteria ( Conlon et al, 2016 ; VandenBerg et al, 2016 ; Pacios et al, 2020 ). Previous research from our laboratory indicated that B. abortus was capable of forming multi-drug tolerant persister cells ( Liu et al, 2023 ) .…”
Section: Resultsmentioning
confidence: 99%
“…These data provide new clues for discovering potential drug targets for clearing Brucella persister cells, as well as for forming new strategies for prevention of Brucella infection. The relationships between the stringent response alarmone (p) ppGpp and persistence are dissimilar in different bacteria (Conlon et al, 2016;VandenBerg et al, 2016;Pacios et al, 2020). Previous research from our laboratory indicated that B. abortus was capable of forming multi-drug tolerant persister cells (Liu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that an E. coli PIMT mutant formed a larger percentage of quiescent, antibiotic-resistant, persister cells than the WT. The authors suggest that in situations where cells cannot repair isoDs, they may respond by becoming persisters, and this may protect cells from the consequences of protein damage (30). This still begs the question of how isoD protein damage might trigger persister formation.…”
Section: Functional Divergence Of Bacterial Pimtsmentioning
confidence: 99%